A111: Expressing FOXP3 in determining the biological characteristics of endometrial adenocarcinomas. Issue 1 (November 2015) - Buchynska, L.; Iurchenko, N.; Verko, N.; Glushchenko, N.
Abstract : Background: According to the "immune-editing" theory, immunocompetent cells being important component of the tumor microenvironment can both show antitumor activity and contribute to the tumor progression. Tumor pathophysiological features affect the structural and functional changes of certain components of tumor microenvironment, in particular, increase the number of T-lymphocytes with regulatory activity (Treg). FOXP3, transcription factor, acts as master regulator for suppressive function of Treg. Recent studies have shown FOXP3 is expressed both in immunocompetent cells and tumor cells; however, the function of this gene in malignant tumors of different genesis is ambiguous (GirdhariLal, et al., 2014). The aim of the study was quantitative assessment of subpopulations CD4+, CD8+, FOXP3+-lymphocytes associated with the tumor, FOXP3+-tumor cells and comparison of these parameters with the clinical and morphological characteristics of endometrial cancer (EC). Materials and methods: A total of 40 EC patients who did not receive special treatment before surgery with the mean age 56.9 ± 2.8 years were included in the study. Morphological and immunohistochemical methods were used in the study (primary monoclonal antibodies: CD4 – clone 4B12, "Millipore", USA, CD8 – clone RIV – 11, "Millipore", USA, FOXP3 – clone 5H5L12, "Invitrogen", USA, Ki-67 - clone MIB1, "DakoCytomation", Denmark) and Real-Time PCR was also used to determine the DNA methylation status of FOXP3 gene mathematical statistics. Results: The dependence of the number of intratumoral CD4+-, CD8+- lymphocytes and FOXP3-lymphocytes on such biological characteristics as the degree of differentiation, growth rate and depth of invasion into the myometrium was established. In endometrial adenocarcinomas, low grade content of FOXP3+ lymphocytes increased (27.8 ± 2.6%), number of intratumoral CD4+ (15, 3 ± 0, 2%), CD8+-lymphocytes (29.6 ± 0.3%) and FOXP3+-tumor cells (15, 5 ± 3, 3%) decreased in contrast to the same parameters in high grade tumors: FOXP3+-lymphocytes (17.4 ± 3.0%), CD4+ (52.0 ± 2.7%), CD8+ (46.4 ± 5.6%), FOXP3+-tumor cells (27.8 ± 2.6%), p < 0.05. DNA analysis of endometrial tumor showed that FOXP3 gene promoter was methylated in 71% of cases. The number of cases with positive methylation status was increasing with lower differentiation grade, that was associated with the low number of FOXP3+-tumor cells. Statistically significant correlation ( p < 0.05) (Spearman rank correlation) was observed between the deep invasion of tumor in myometrium and the number of FOXP3+-tumor cells ( R = −0.63), number of FOXP3+- and CD4+-lymphocytes ( R = 0.68 and R = −0.55, respectively) as well as the level of tumor proliferative activity ( R = 0.74). Conclusion: Quantitative changes of some components of the tumor microenvironment such as CD4+-, CD8+-, FOXP3+-lymphocytes and content of FOXP3+-tumor cells correlate with the biological characteristics of EC and apparently have a significant role in the progression of this cancer.